2017
DOI: 10.1055/s-0043-100762
|View full text |Cite
|
Sign up to set email alerts
|

Update Opipramol

Abstract: Opipramol was developed in the 1960s as an antidepressant and has chemical similarities with tricyclic antidepressants. Pharmacodynamic properties with absent reuptake inhibition of serotonin and noradrenaline and agonism at sigma receptors distinguish opipramol from tricyclics. Furthermore, antidepressive effects are smaller than the anxiolytic ones. The mechanism of action of opipramol is currently not sufficiently understood. Agonistic effects at sigma receptors have been linked with therapeutic effects. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Opipramol diHCl (OPI): OPI was developed originally as an antidepressant and later used as a treatment for somatoform disorder ( Gahr et al, 2017 ). The sigma receptor agonist did not affect HR in myl7:eGFP or change HS ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Opipramol diHCl (OPI): OPI was developed originally as an antidepressant and later used as a treatment for somatoform disorder ( Gahr et al, 2017 ). The sigma receptor agonist did not affect HR in myl7:eGFP or change HS ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, DLX dose-dependently increased the ToxScore, resulting in complete lethality at 80 µM (Figure 6C). Opipramol diHCl (OPI): OPI was developed originally as an antidepressant and later used as a treatment for somatoform disorder (Gahr et al, 2017). The sigma receptor agonist did not affect HR in myl7:eGFP or change HS (Figure 4A).…”
Section: Pyrvinium Pamoate (Pp)mentioning
confidence: 99%
“…Vielmehr wirkt Opipramol hauptsächlich durch eine Bindung an σ-Rezeptoren mit der Folge einer Modulation im NMDA-System (NMDA: N-Methyl-D-Aspartat). Aufgrund der vor allem anxiolytischen sowie sedierenden Wirkung kommt Opipramol häufig zur Behandlung von Angsterkrankungen, Unruhe und Schlafstörungen und eher seltener zur antidepressiven Therapie zur Anwendung [5,13,14]. [16].…”
Section: Opipramolunclassified
“…Opipramol (IS-opi) is a member of tricyclic antidepressants (TCAs) [Korobkova et al 2010] and was developed in the 1960s (Gahr et al 2017). Typically used in the treatment of generalized anxiety disorder (GAD) and somatoform disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Most TCAs act as monoamine reuptake inhibitors, but opipramol does not, and instead acts primarily as a sigma receptor agonist. It was reported that opipramol was metabolized by P450 2D6 (Gillman 2007;Gahr et al 2017). In plasma and urine was identified oxidation product of the hydroxyethyl moiety to an acetic acid group at the piperazine side chain, decarboxylation products, opipramol-N-oxide, deshydroxyethyl metabolite, and dibenzoazepine.…”
Section: Introductionmentioning
confidence: 99%